Study and Design of Fuzzy Logic and Its Application in Traffic Control - Basanti Muzalda, Arihant Jain (Mathematical Statistician and Engineering Applications, 2023)
The growth in the number of automobiles on the road, combined with a shortage of available road space, has resulted in traffic congestion in many areas. Congestion has a negative impact on production, diminishes efficiency, and resulting in loss of energy. As a result of the traffic signal system in place at intersections, this bottleneck is worsened to a significant degree. Because a standard traffic system does not take into account the fluctuation in traffic signal time lengths, it is impossible to maximize its efficiency. The use of our proposed fuzzy traffic signal management system may be able to decrease traffic congestion. Instead of a predetermined amount of time, it takes into consideration the current density of traffic at the intersection while deciding the duration of the green light period. As a result of our optimization of the duration of the green light time, our system is better equipped to handle congestion than other systems. In recent years, many studies have been undertaken on fuzzy traffic control systems, even though there are many more intricate systems available in the literatures.